Preliminary Phytochemical Screening (Qualitative Analysis) of Cacao Leaves (Theobroma cacao L.) - Hesty Parbuntari; Yona Prestica; Rizki Gunawan; Meri Novia Nurman; Fransiska Adella (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
One of the important processes of cocoa plants growing is pruning. It aims to eliminate sick, broken, or the appearance of water buds disturbing the cacao production. The period of pruning is varios. The various periods of pruning lead to leave wide waste of leaves, stems, and twigs. Yet the waste would not been used to other activities, only a small portion of the waste used as natural fuel (stems and twigs) and cocoa leaves waste as animal feed. Phytochemicals naturally present in every part of plants range from leaves, stem bark, fruits to roots. Secondary metabolites are natural products from plants which include alkaloid, flavonoid, steroid, terpenoid, sapponin compounds, etc. This study performed some phytochemical characterisations. It have confirmed that cacoa leaves consist some of bioactives compounds which are potential for furhter activities in pharmaceutical disease.